Actos de guerra. Tiempos y escenas para pensar Malvinas - Marcela Visconti (Centre de Recherches sur les Mondes Américains, 2019)
In the last few years, around the 30th anniversary of the Malvinas War between Argentina and the United Kingdom there was an explosion of cultural productions about the war experience, with various proposals and formats which, besides drama, film, and literature, include TV shows, short-feature films, educational materials, and opera. I will focus on some examples which prove significant when reflecting about the documentary value of bodies, particularly as regards the recent work by Lola Arias (the documentary Teatro de guerra, the play Campo minado, and the video-installation Veteranos), and about the symbolic power of absent bodies, particularly in the opera Aliados, una ópera en tiempo real, by Sebastián Rivas and Esteban Buch, which premiered in Buenos Aires in 2015 directed by Marcelo Lombardero. At the performative boundary between heterogeneous materials, and based on cross-contaminating genres and diverse languages, these works construct a scene that looks back on the war past to bring it to the present. In this context of temporal tension, the presence of the documentary-real, gives rise to a space in which, through bodies (or the absence thereof), History breaks through.